Long-term forest succession improves plant diversity and soil quality but not significantly increase soil microbial diversity: Evidence from the Loess Plateau - Liu, Yulin; Zhu, Guangyu; Hai, Xuying; Li, Jiwei; Shangguan, Zhouping; Peng, Changhui; Deng, Lei (Ecological engineering, 2020)
Many studies have focused on the processes of vegetation succession, however, the dynamics of soil microbes and the synergy between vegetation and soil are still poorly understood following vegetation succession. This study focused on a forest succession sequence including farmland, grassland, shrubland (i.e., Hippophae rhamnoides), pioneer forest (i.e., Populus davidiana), and climax forest (i.e., Quercus liaotungensis) on the Loess Plateau of China, to explore plant and soil changes, as well as soil microbial community dynamics. The results showed that litter biomass, soil organic carbon (SOC), total nitrogen (TN) and the ratio of SOC to TN exhibited an increasing trend in the whole process of the forest succession, and NH4+, microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), and the ratio of dissolved organic carbon (DOC) to dissolved organic nitrogen (DON) had significantly increased before the shrubland stage, and then they were going to be stable. During the forest succession, the main bacterial phyla present were Proteobacteria, Actinobacteria, and Acidobacteria, and the predominant fungal phyla were Ascomycota and Basidiomycota. The soil microbial community composition was stable and did not change significantly, but the bacteria and fungal communities were associated with specific plant or soil properties. It was proved that the change of soil microbial community was closely related to vegetation and soil community changes. The results suggested that long-term forest succession not only improves plant diversity, but also improves soil biology and quality, even though it does not significantly increase soil microbial diversity. The findings enhance the understanding of the impact of soil microbial ecological characteristics and provide an important guidance for the sustainable management of forest ecosystems following long-term natural vegetation restoration. •Plant diversity and soil properties improved in response to vegetation succession.•Soil microbial community did not change significantly during vegetation succession.•Changes in plant, soil did not result in synchronized effects on microbial community.•Litter, root, DOC, DON played critical effects on soil microbial community change.